Determination of effectiveness of commercial fishermens in 2014 in turkey by data envelopment analysis - Ferhan Kaygısız; Atıf Evren (Eurasian Journal of Veterinary Sciences)
Aim: Considering the productive efficiency of large-scaled fishermen in Turkey and thus contributing to the increase of them is the main concern of this study. Materials and Methods: The records of Turkish Statistical Institute (TSI) about fishing vessels were used in order to analyze the research. These records include the economical inputs of 13m long and above fish-hunting vessels in Turkey, in 2014 as the production year. In the study, 107 vessels were determined by random sampling method. Data Envelopment Analysis (DEA) was used in order to evaluate the efficiency. In DEA, data was analyzed in accordance with the input-oriented, constant returns to scale model (CRS). Fuel-oil, labor force, repair and maintenance, victualing, ice-box, clothing, other expenses and fixed asset expenses were considered as input whereas fish income as an output. Results: The results of the analysis indicated that 27% of the fishermen were efficient. Suggested potential improving percentages were identified to be able to turn the inefficient fishermen to efficient. It was pointed out that if the percentages of fuel oil, labor force, repair and maintenance, victualing, box-ice, clothing, other and fixed expenses increase to 59.27%, 55.93%, 60.87%, 51.17%, 43.17%, 64.19%, 59.50% and 60.14% respectively, they would reach to an efficient level. Conclusion: Decreasing input expenses of fishery institutions and rising the rivalry, government stimulation and support should be continued to increase to solve problems. Moreover, alongside providing education to fishermen, fishery cooperatives can be empowered and encouraged to work actively to form an organization.